2006
DOI: 10.1002/oa.846
|View full text |Cite
|
Sign up to set email alerts
|

Dental status of Napoleon's Great Army's (1812) mass burial of soldiers in Vilnius: childhood peculiarities and adult dietary habits

Abstract: A mass grave of the soldiers of Napoleon's Great Army, containing no less than 3269 individuals who died during the retreat from Russia in December 1812, was uncovered during an archaeological rescue excavation in 2002 in Vilnius, Lithuania. General dental analysis, including that of dental wear, tooth loss, caries, calculus, and periodontal diseases and abscesses, was used to evaluate the oral health status and possible dietary patterns of individuals who represented recruits from almost all of Western and Ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…AMTL results from many causes, including dental caries, periodontal disease, attrition, trauma, and ritual tooth extraction; however, it has been suggested that AMTL is often caused by dental caries (Sakura, 1964;Lukacs, 1995;Hillson, 2001;Cucina and Tiesler, 2003;Palubeckaite et al, 2006;Oyamada et al, 2007a). In the case of Kumejima, a tradition of ritual tooth extraction did not exist and no large battles took place in the early-modern times that may have resulted in trauma-related tooth loss (Nakahara, 1990;Doi, 2003;Uezu, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AMTL results from many causes, including dental caries, periodontal disease, attrition, trauma, and ritual tooth extraction; however, it has been suggested that AMTL is often caused by dental caries (Sakura, 1964;Lukacs, 1995;Hillson, 2001;Cucina and Tiesler, 2003;Palubeckaite et al, 2006;Oyamada et al, 2007a). In the case of Kumejima, a tradition of ritual tooth extraction did not exist and no large battles took place in the early-modern times that may have resulted in trauma-related tooth loss (Nakahara, 1990;Doi, 2003;Uezu, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, many authors have investigated the prevalence and timing of LEH in a range of prehistoric cranial series (e.g. Guatelli-Steinberg and Lukacs, 1999;Cucina et al, 2006;Larsen, 2006;Palubeckaite et al, 2006;Belcastro et al, 2007;Boldsen, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Deerr (1950) estimates the sugar consumption in kilograms per person per year had increased from 1.8 kg in 1700 to 3.6 kg in 1750, reaching 8.2 kg per person by 1800. In Britain, sugar consumption per person had reached 6.7 kg/annum by 1792 (Palubeckaite et al 2006), indicative of growing rates of sugar consumption throughout the eighteenth century (Mitchell and Deane 1962). Later, the British doubled their consumption of sugar during the nineteenth century (Deerr 1950), consuming mostly cane sugar imported from the Caribbean Sea.…”
Section: Carbohydrates and Dental Cariesmentioning
confidence: 99%
“…Many researchers posit that an increased dependence upon carbohydrates and the introduction of refined sugars have increased the rates of caries diachronically for many human groups (e.g., Burt 1993;Hardwick 1960;Mayhall 1970;Miura et al 1997;Moore 1993;Oranje et al 1935-37;Palubeckaite et al 2006;Price 1936;Russell et al 1961;Saunders et al 1997;Whittaker and Molleson 1996).…”
Section: Carbohydrates and Dental Cariesmentioning
confidence: 99%
“…Periodontal disease is one of the most common chronic diseases in living populations (Abdellatif and Burt, 1987), with severe forms affecting an estimated 10-15% of people worldwide and mild forms of the disease affecting as much as 90% of people in some populations (Beck et al, 1996;Pihlstrom et al, 2005). Numerous bioarchaeological investigations have also identified periodontal disease at varying frequencies in skeletal samples from past populations (e.g., Clarke et al, 1986;Kerr, 1994;Chazel et al, 2005;Eshed et al, 2006;Oztunc et al, 2006;Palubeckaite et al, 2006;Lieverse et al, 2007).…”
mentioning
confidence: 97%